2019
DOI: 10.1093/mnrasl/slz056
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the circularity problem in the Ep−Eiso correlation of gamma-ray bursts

Abstract: We here propose a new model-independent technique to overcome the circularity problem affecting the use of gamma-ray bursts (GRBs) as distance indicators through the use of Ep−Eiso correlation. We calibrate the Ep−Eiso correlation and find the GRB distance moduli that can be used to constrain dark energy models. We use observational Hubble data to approximate the cosmic evolution through Bézier parametric curve obtained through the linear combination of Bernstein basis polynomials. In doing so, we build up a n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
124
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(137 citation statements)
references
References 41 publications
13
124
0
Order By: Relevance
“…These GRB luminosity indicators have been widely used as standard candles for cosmology research (Schaefer 2007;Wang et al 2007;Amati et al 2008;Amati & Della Valle 2013;Wei et al 2013;Wang et al 2017;Amati et al 2019;Muccino et al 2021;Montiel et al 2021), and it has been shown that when combined with other probes, GRBs can indeed extend the Hubble diagram to higher redshifts and help to make better constraints on cosmological parameters (Amati & Della Valle 2013;Wang et al 2015, for a review). However, since the observed GRB rate falls off rapidly at low redshifts, it is very difficult to make a robust calibration for those GRB correlations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These GRB luminosity indicators have been widely used as standard candles for cosmology research (Schaefer 2007;Wang et al 2007;Amati et al 2008;Amati & Della Valle 2013;Wei et al 2013;Wang et al 2017;Amati et al 2019;Muccino et al 2021;Montiel et al 2021), and it has been shown that when combined with other probes, GRBs can indeed extend the Hubble diagram to higher redshifts and help to make better constraints on cosmological parameters (Amati & Della Valle 2013;Wang et al 2015, for a review). However, since the observed GRB rate falls off rapidly at low redshifts, it is very difficult to make a robust calibration for those GRB correlations.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid the circularity problem, it has been proposed to use SN Ia data in the same redshift range as GRBs to calibrate their luminosity correlations (Liang et al 2008;Vitagliano et al 2010;Gao et al 2012). Considering that objects at the same redshift should have the same luminosity distance in any cosmology, one can assign the distance moduli of SN Ia to GRBs at the same redshifts (Liang et al 2008;Demianski et al 2017a), or one can use the SN Ia data to fit the model-independent cosmography formula that reflects the Hubble relation between the luminosity distance and redshift, and then obtain the GRB luminosity distance (Gao et al 2012;Amati et al 2019). In this way, one can derive a cosmology-independent calibration for the GRB candles.…”
Section: Introductionmentioning
confidence: 99%
“…In this range there are a handful of data sets. These include HIIG starburst galaxy data that reach to ∼ 2.4 (Siegel et al 2005;Plionis et al 2009;Mania & Ratra 2012;Chavez et al 2014;González-Morán et al 2019;Cao et al 2020a,b), quasar angular size measurements that reach to ∼ 2.7 (Gurvits et al 1999;Chen & Ratra 2003a;Cao et al 2017;Ryan et al 2019;Cao et al 2020a,b), and gamma-ray burst observations that reach to ∼ 8.2 (Lamb & Reichart 2000;Wang et al 2016;Demianski et al 2019;Amati et al 2019;Fana Dirirsa et al 2019;Muccino 2020;Luongo & Muccino 2020;Khadka & Ratra 2020c;Cao et al 2020b). Quasar (QSO) X-ray and UV flux measurements that reach to ∼ 7.5 provide another set of data that probe this intermediate redshift region (Risaliti & Lusso 2015Yang et al 2019;Velten & Gomes 2020;Wei & Melia 2020;Lindner et al 2020;Zheng et al 2020;Mehrabi & Basilakos 2020;Khadka & Ratra 2020a,b;Lusso et al 2020;Rezaei et al 2020;Speri et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…But we want to use the observed properties of GRBs to derive the cosmological parameters. Several procedures to overcome this circular situation have been proposed (see for instance, Schaefer, 2007;Basilakos and Perivolaropoulos, 2008;Demianski et al, 2011;Amati et al, 2019).…”
Section: Gamma-ray Burst Hubble Diagrammentioning
confidence: 99%